Groundwater markets in Pakistan: participation and productivity - Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 1996)
In Pakistan, where agriculture is heavily dependent on irrigation, informal water markets are an increasingly important way to provide small farmers and tenant farmers with access to ground- water. The public canal irrigation system provides water to farmers who own land within designated areas, but it does not provide all farmers with adequate water supplies when they need it. Therefore, farmers who can afford it are installing tubewells as a sole or supplementary source of irrigation (Figure 1). Despite the growth in private tubewells, ownership remains limited to a relatively small percentage of farmers. Some well owners also sell groundwater to other nearby farmers. The resulting localized, informal markets have become an important source of irrigation for many farmers. Although selling water from private wells is a long-standing practice in South Asia, these informal arrangements are only now being examined in detail. As water becomes scarce or degraded, more information is needed to help Pakistan and other South Asian countries make policy decisions that will improve equity of access to groundwater resources. Groundwater Markets in Pakistan: Participation and Productivity, Research Report 105, by Ruth Meinzen-Dick, looks at how water markets operate, who participates, the nature of the transactions, and the effects of the markets on agricultural productivity and incomes, in order to determine what helps or hinders the emergence of viable water markets. The report reviews the current literature on groundwater markets, the empirical evidence on performance, and the available policy options. The study examines patterns of private tubewell and groundwater market development using district-level data for the country as a whole, then looks in detail at the performance of groundwater markets using farm household data collected in an IFPRI survey conducted in 1990-92.